The additive effect of the stress hyperglycemia ratio on type 2 diabetes: a population-based cohort study - Cancan Cui; Jiayin Song; Lingyu Zhang; Ning Han; Wanqi Xu; Chen Sheng; Guangda Xin; Xiaofeng Cui; Lili Yu; Lin Liu (Cardiovascular Diabetology)
Abstract Background The stress hyperglycemia ratio (SHR) has recently gained attention as a marker for acute hyperglycemia, which has been linked to adverse clinical outcomes. However, its independent role in the development of type 2 diabetes (T2D) remains understudied. This cohort study aimed to assess the association between SHR and the incidence of T2D. Methods The study included 8978 participants aged 45 or older, free of diabetes at baseline, from the China Health and Retirement Longitudinal Study (CHARLS). Incident T2D up to December 31, 2020, was the primary outcome. Participants were divided into SHR quartiles, and Cox proportional hazards regression and fine-gray competing risk models were used to assess SHR’s association with T2D onset, adjusting for fasting glucose and HbA1c. Results The mean age of participants was 59.0 ± 9.5 years, and 51.5% were women. Over a mean follow-up of 7.8 years, 1084 participants developed T2D. Cox regression analysis revealed that individuals in the highest SHR quartile had a significantly higher risk of T2D onset compared to those in the lowest quartile (HR 1.48, 95% CI 1.26–1.75, P for trend < 0.001). Stratified analyses by sex, obesity, and smoking showed consistent results. Adding SHR to fasting glucose and HbA1c models improved the AUC for T2D prediction (DeLong Test, P = 0.013). Conclusion SHR is independently associated with incident T2D, suggesting its potential use in the risk stratification and prediction for T2D, beyond glucose and HbA1c.